2017
DOI: 10.15252/embr.201643078
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodelling factor ATRX suppresses R‐loops in transcribed telomeric repeats

Abstract: ATRX is a chromatin remodelling factor found at a wide range of tandemly repeated sequences including telomeres (TTAGGG) ATRX mutations are found in nearly all tumours that maintain their telomeres via the alternative lengthening of telomere (ALT) pathway, and ATRX is known to suppress this pathway. Here, we show that recruitment of ATRX to telomeric repeats depends on repeat number, orientation and, critically, on repeat transcription. Importantly, the transcribed telomeric repeats form RNA-DNA hybrids (R-loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 45 publications
4
118
0
Order By: Relevance
“…Telomeres are composed of repetitive DNA with high G/C contents and thus prone to form secondary structures including telomeric RNA‐DNA hybrids (R‐loop) and G‐quadruplex structures (Sundquist & Klug, ; Balk et al , ). These high‐order structures are known to pose threats to the processivity of the replication machinery and can recruit ATRX (Law et al , ; Clynes et al , ; Nguyen et al , ). Those realizations, together with the finding that re‐expression of ATRX in ATRX ‐null cells could strongly repress ALT‐associated activities (Clynes et al , ; Napier et al , ), fueled a speculation that ATRX might function directly to suppress ALT by resolving those secondary structures during telomere replication (Leung et al , ; Clynes et al , ; Nguyen et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telomeres are composed of repetitive DNA with high G/C contents and thus prone to form secondary structures including telomeric RNA‐DNA hybrids (R‐loop) and G‐quadruplex structures (Sundquist & Klug, ; Balk et al , ). These high‐order structures are known to pose threats to the processivity of the replication machinery and can recruit ATRX (Law et al , ; Clynes et al , ; Nguyen et al , ). Those realizations, together with the finding that re‐expression of ATRX in ATRX ‐null cells could strongly repress ALT‐associated activities (Clynes et al , ; Napier et al , ), fueled a speculation that ATRX might function directly to suppress ALT by resolving those secondary structures during telomere replication (Leung et al , ; Clynes et al , ; Nguyen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, ATRX and its binding partner DAXX are known to form a histone variant H3.3‐specific chaperone complex that orchestrates replication‐independent nucleosome assembly at repetitive heterochromatic DNA regions including telomeres (Drane et al , ; Goldberg et al , ; Lewis et al , ; Elsasser et al , ; Voon et al , ). Besides its histone H3.3 depositing function, ATRX has also been implicated in the process of telomere DNA replication by facilitating resolution of telomere cohesion, R‐loops, and G‐quadruplex structures (Law et al , ; Clynes et al , ; Ramamoorthy & Smith, ; Nguyen et al , ). Given the fact that telomere length maintenance is essential for cell immortalization and tumorigenesis, the high concordance of ATRX deficiency with ALT activation has hence prompted the speculation that ATRX may exert its tumor suppressor function by directly repressing ALT (Pickett & Reddel, ; Maciejowski & de Lange, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this prediction, in vitro studies demonstrated that plasmids containing human telomeric repeats form RLs with telomere‐containing RNA transcribed off the C‐rich strand . Utilizing the S9.6‐DNA:RNA hybrid‐specific antibody, human TRLs were observed in cancer cells, in particular those that maintain their telomeres by the ALT pathway , as well as in cells of patients with immunodeficiency, centromeric instability and facial anomalies (ICF) syndrome . In both ALT and ICF cells, abnormally high levels of TERRA are transcribed , explaining the high levels of TRLs detected in these cells.…”
Section: Telomere R‐loops In Mammalsmentioning
confidence: 87%
“…D). Recently, it was demonstrated that the damaging secondary structures that ATRX acts to resolve are actually products of TRLs . This study revealed that factors that influence TRL generation such as telomere length, repeat orientation, and TERRA transcription levels impact the degree by which ATRX is recruited to telomeres.…”
Section: Telomere R‐loops In Mammalsmentioning
confidence: 96%